Building The Strengthening of Environmental Protection and Management In The Industrial Revolution-Era 4.0 - Adi Gunawan; Nadir Nadir; Fatkhurohman Fatkhurohman (SASI, 2022)
Introduction: Environmental protection is no longer negotiable, in Indonesia and internationally the destruction of the environment due to mining and deforestation has reached an alarming threshold and threatens the lives of future generations. The actions that have been taken and the existence of institutions / organizations in the field of environment are not able to make a maximum contribution to environmental protection.